The Effects of Melittin Coding Gene of Bee Venom on Bcl-2 and Bax Genes Expression in ACHN Cells - Erfaneh Heidari Esfahani; Abbas Doosti (Negah Institute for Scientific Communication, 2021)
Introduction: Venom therapy is a traditional procedure for cancer treatment. Various types of natural compositions in bee venom indicate an area of research for therapeutic and anti-cancer purposes. Melittin is a cationic and amphipathic peptide that interferes with lipid-protein molecular interactions in cell membranes leading to cell lysis. Melittin also prevents metastasis in hepatocarcinoma through inhibition of cell migration. This study aimed to investigate the expression of Bcl-2 and Bax genes in ACHN cells transfected with a recombinant vector carrying bee melittin gene by real-time RT-PCR technique.  Methods: In the present study, the recombinant plasmid of pcDNA3.1(+)-melittin was designed. Then, the synthesized gene was cloned into the pcDNA3.1(+) vector. Following plasmid amplification, PCR assay and enzymatic digestion method were used to approve the accuracy of plasmid amplification. ACHN cells were cultured, and sham and control groups were also prepared. RNA was extracted from the treatment and control groups using RNX-Plus solution. cDNA was generated using a specific laboratory kit. A real-time RT-PCR assay was performed to evaluate the expression of Bcl-2 and Bax genes in ACHN cells transfected with recombinant vector. Finally, the obtained data were analyzed using SPSS. Results: The expression of the Bax gene significantly (P=0.03) increased in pcDNA3.1(+)-melittin compared to the pcDNA3.1(+) group. Bcl-2 gene expression showed a significant decreasing trend in the experimental group of pcDNA3.1(+)-melittin (P=0.001) compared to the pcDNA3.1(+).  Conclusion: According to the obtained results, the expression of Bax and Bcl-2 genes in the ACHN cell line can be affected by the melittin gene of bee venom. Thus, bee venom as a natural substance with its anti-cancer properties can be considered for further experimental investigations.